2022
DOI: 10.3390/su142215131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intra-Industry Trade, Foreign Direct Investment, and Renewable Energy on Portuguese Carbon Dioxide Emissions

Abstract: This paper revisited the link between intra-industry trade (IIT) between Portugal and Spain and Portuguese carbon dioxide (CO2) emissions. The research also considers the effects of foreign direct investment (FDI) on CO2 emissions, pondering the arguments of the pollution haven hypothesis and the halo hypothesis. As an econometric strategy, this investigation has applied panel data, namely a Pooled Mean Group of an Autoregressive Distributed Lag (ARDL) model and Panel Quantile Regression (PQR). The preliminary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Using the methodology of Pedroni (2001) of panel cointegration, it is possible to see in Table 5 that the variables in studies are cointegrated in the long run. In Table 6, we use the multicollinearity test based on the variance inflation factor (VIF) by the variables considered in this research (Portuguese income per capita, investors income per capita, similar language of ex-colonies (Lang), and geographical distance (LogGDIST).We can conclude that the variables have no problems of collinearity, considering the argument referred to by Leitão et al (2022), andFuinhas et al (2021), i.e., the variance inflation factor (VIF) is less to 5. Considering that the sample uses panel data, one of the appropriate tests to evaluate autocorrelation is the test proposed by Arellano and Bond (1991), determined based on the first differences.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Using the methodology of Pedroni (2001) of panel cointegration, it is possible to see in Table 5 that the variables in studies are cointegrated in the long run. In Table 6, we use the multicollinearity test based on the variance inflation factor (VIF) by the variables considered in this research (Portuguese income per capita, investors income per capita, similar language of ex-colonies (Lang), and geographical distance (LogGDIST).We can conclude that the variables have no problems of collinearity, considering the argument referred to by Leitão et al (2022), andFuinhas et al (2021), i.e., the variance inflation factor (VIF) is less to 5. Considering that the sample uses panel data, one of the appropriate tests to evaluate autocorrelation is the test proposed by Arellano and Bond (1991), determined based on the first differences.…”
Section: Resultsmentioning
confidence: 91%
“…Following the empirical works of Paniagua et al (2015), Alotaibi and Alajlan (2021), and Leitão et al (2022), we decided to apply the panel quantile regressions method suggested by Koenker and Bassett (1978) to the gravity model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for a positive association between FDI and GHG could be the role of the former in stimulating industrial activity and the surge in energy consumption leading to an increase in the latter. FDI has an adverse effect on ES by affecting carbon emission efficiency [60,61].…”
Section: Economic Policy Uncertainty-ghg Model Resultsmentioning
confidence: 99%
“…Regardless of the geographic area or the organization of the data (panel data or time series), the studies by Mahmoodi and Dahmardeh [5], Leitão et al [6], and Gyamfi et al [7] demonstrate the importance of continuing to study the EKC. Furthermore, in addition to the relationship between economic growth and polluting emissions, it is noted that in recent years, researchers have more frequently introduced into econometric models as explanatory variables not only the consumption of fossil energies but also the consumption of renewable energies and the energetic capacity.…”
Section: Introductionmentioning
confidence: 99%